Efeito hormese e manejo de isolados de Lasiodiplodia theobromae resistentes a tiofanato-metílico - SILVA, Erivaldo Laurentino da (2020)
Peduncular rot caused by Lasiodiplodia theobromae is one of the main diseases in papaya crop (Carica papaya) and resistance to the fungicide thiophanate-methyl has been found in isolates of this pathogen in Brazilian Northeast. Therefore, the aim of this study was to evaluate the sensitivity of L. theobromae resistant isolates and the effectiveness of different fungicides, and to investigate the hormesis effect induced by fungicide in populations of the pathogen, aiming at alternatives to manage this important disease. In vitro and in situ assays were performed, using fungicides that are registered and not registered for papaya crop. Demethylation inhibitors fungicides were more effective to control resistant isolates in vitro, and imazalil, metconazole and tebuconazole were also effective to control the rot. On the other hand, thiabendazole registered to control the disease in postharvest was ineffective in controlling rot caused by the resistant isolate, besides providing an increase in its aggressiveness. Stimuli induced by thiophanate-methyl on mycelial growth and the aggressiveness of the resistant isolate were observed. The ineffectiveness of control observed in this study associated with the occurrence of stimuli on mycelial growth and pathogen aggressiveness in the presence of fungicides indicates the need for new strategies to manage the disease in areas with a history of resistance. The fungicide imazalil, registered for postharvest of papaya, is a good option to control L. theobromae isolates. Metconazole and tebuconazole, although not registered for this crop, have potential to manage the disease in areas with a history of resistance to thiophanate-methyl.